Identification of a Small TAF Complex and Its Role in the Assembly of TAF-Containing Complexes - Demény, Màté A. (Public Library of Science, 2007)
TFIID plays a role in nucleating RNA polymerase II preinitiation complex assembly on protein-coding genes. TFIID is a multisubunit complex comprised of the TATA box binding protein (TBP) and 14 TBP-associated factors (TAFs). Another class of multiprotein transcriptional regulatory complexes having histone acetyl transferase (HAT) activity, and containing TAFs, includes TFTC, STAGA and the PCAF/GCN5 complex. Looking for as yet undiscovered subunits by a proteomic approach, we had identified TAF8 and SPT7L in human TFTC preparations. Subsequently, however, we demonstrated that TAF8 was not a stable component of TFTC, but that it is present in a small TAF complex (SMAT), containing TAF8, TAF10 and SPT7L, that co-purified with TFTC. Thus, TAF8 is a subunit of both TFIID and SMAT. The latter has to be involved in a pathway of complex formation distinct from the other known TAF complexes, since these three histone fold (HF)-containing proteins (TAF8, TAF10 and SPT7L) can never be found together either in TFIID or in STAGA/TFTC HAT complexes. Here we show that TAF8 is absolutely necessary for the integration of TAF10 in a higher order TFIID core complex containing seven TAFs. TAF8 forms a heterodimer with TAF10 through its HF and proline rich domains, and also interacts with SPT7L through its C-terminal region, and the three proteins form a complex in vitro and in vivo. Thus, the TAF8-TAF10 and TAF10-SPT7L HF pairs, and also the SMAT complex, seem to be important regulators of the composition of different TFIID and/or STAGA/TFTC complexes in the nucleus and consequently may play a role in gene regulation.